Comparison of PuraStat self-assembling peptide hydrogel versus mineral-based Hemospray for endoscopic hemostasis of upper and lower gastrointestinal lesions in pigs - Gil, Eun Seok; O’Neill, Kate; Aleksi, Elton; Budrewicz, Jay; Melidone, Raffaele; Spirio, Lisa (Frontiers in Gastroenterology, 2022)
Objective: To compare a RADA16-based self-assembling peptide hydrogel versus an inorganic powder-based spray device for controlling postoperative bleeding in upper and lower GI mucosal lesions in pigs. Methods: Multiple mucosal lesions were endoscopically-created in the stomachs and lower colons of six Yorkshire swine on Day 0. Three animals’ wounds were treated with 2.5% RADA16 solution (PuraStat®), two animals were treated with an aerosolized mineral powder (Hemospray®), and one animal was an untreated control. Primary outcomes were test article applications required to control initial bleeding, time-to-hemostasis, and rebleeding incidence. Secondary outcomes included animal recovery, and clinical pathology at weekly endoscopic evaluations and the 4-week study terminus. Results: Number of material administrations required and time-to-hemostasis was comparable between PuraStat and Hemospray groups. Rebleeding rates were comparable between treatments. Two of 12 (17%) Hemospray and none of 18 (0%) PuraStat stomach sites experienced rebleeding during the final 4 min of the 10 min observation period. No delayed bleeding was observed during weekly endoscopic follow-ups. Hematology and serology values remained normal in all animals. Histology showed expected healing responses at all PuraStat- and Hemospray-treated defects, with less inflammation than untreated sites. Histomorphological observations were comparable between different groups for both the stomach and colon for test and control materials, with lower inflammation scores than untreated sites. Performance and usability responses were generally good with both systems, although the Ability to Treat Intended Site score was significantly better with PuraStat in upper GI lesions. Conclusions: PuraStat and Hemospray were effective topical hemostats for mild-to-moderate bleeding in upper and lower GI wounds. Rebleeding was observed in two of 12 Hemospray-treated sites and none of 18 PuraStat-treated sites. PuraStat and Hemospray were associated with better wound healing than untreated controls. The ability to treat upper GI lesions was easier with the PuraStat versus Hemospray system.